2006
DOI: 10.1177/1368431006063343
|View full text |Cite
|
Sign up to set email alerts
|

Technological Zones

Abstract: This article provides an overview of the analysis of technological zones. A technological zone can be understood as a space within which differences between technical practices, procedures and forms have been reduced, or common standards have been established. Such technological zones take broadly one of three forms: (1) metrological zones associated with the development of common forms of measurement; (2) infrastructural zones associated with the creation of common connection standards; and (3) zones of quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
180
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(191 citation statements)
references
References 24 publications
2
180
0
9
Order By: Relevance
“…The smart meter data resolution now set by the SMETS may also be sub-optimal for development of feedback devices drawing on practice theory design concepts. This finding is in keeping with other studies of standard-setting, where the breadth of expertise found amongst standard-setters is similarly limited, resulting in significant negative implications for outcomes (Barry 2006;Lovell 2014).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The smart meter data resolution now set by the SMETS may also be sub-optimal for development of feedback devices drawing on practice theory design concepts. This finding is in keeping with other studies of standard-setting, where the breadth of expertise found amongst standard-setters is similarly limited, resulting in significant negative implications for outcomes (Barry 2006;Lovell 2014).…”
Section: Resultssupporting
confidence: 77%
“…There was only one response from a member of the public. This fits with findings from other studies of standards setting (Bowker and Star 2000;Barry 2004Barry , 2006Lovell 2014) of its closed, technical and therefore anti-political character: through expertise and the associated use of dense technical language, the development of the SMETS has effectively excluded wider public debate and discussion, in particular by the vital 'consumers'/householders with whom the SMI Programme is ostensibly concerned. This is returned to in the discussion in Section 6.…”
Section: Standards In the Uk Smi Programmesupporting
confidence: 69%
“…Borders are thought of less as being continuous linear structures enclosing a political territory and demarcating a state's external edges, and more as being zones, bands, nodes, and filters. Indeed scholars now talk of a 'virtual border' (Freudenstein, 2001), and 'indeterminate' (Bigo, 2003) and 'technological' zones (Barry, 2006). These changes are referred to in terms of the 'proliferation' of borders and 'delocalization of control' (Rigo, 2005) in order to indicate that the control, once located at the borders, is now exercised by a variety of means and in a variety of locations.…”
Section: Transformationsmentioning
confidence: 99%
“…To our two previous arguments-(1) for a symmetrical valuation of social methods, and (2) a broadening of the range of social devices and appoaches taking part in environmental change-we then add the environmental specificity of methological invention-to the environmental specificity of interventions of and by methods as our third point. In investigating this, we think it fruitful to draw not only from the STS tradition-which has been so important in rendering us sensitive to the materiality and performativity of methods-but equally from the literature that has sensitized us to the ways in which objects are being modified and transformed as they move (by way of a heterogeneous set of practices) from one context, setting, or practice to another (Barry, 2006). The implication is that the specificity of the sites and settings for enacting environmental change matter and their particular capacities for articulating environments as account-able require further investigation.…”
Section: The Many Politics Of Social Methods: From Surveys To Particimentioning
confidence: 99%